Intertextuality as semiotic mediation for youth’s enactment of agency and identity in everyday digital literacy practices - Ahmad Budairi (English Language Teaching Educational Journal, 2022)
The purpose of this research is to investigate the practice of intertextuality of Farah (pseudonym) a 20-year-old female university student who engaged in a variety of culturally shaped digital literacy practices. In particular, it seeks to elucidate how Farah’s practice of intertextuality serves as a semiotic mediation for her exercise and enactment of agency and identity during her everyday literacy practice on Instagram. This research was framed as a case study design with a connective ethnography approach specifically suited to the online environment and digital communication where the researcher’s physical presence as an observer is no longer required. Data were collected by means of digital media and technology such as WhatsApp Message Service, informal phone interviews, and online observation. The collected data comprised online snapshots of quote bots, pictures, drawings and comments that Farah produced and shared as part of her everyday digital literacy practice. The data analysis entailed examination of Farah’s practice of intertextuality through the lens of sociocultural perspective on text production and interpretation. The findings revealed that Farah’s use of quote bots and doodles posted on Instagram involved the act of borrowing texts from other sources as well as mixing English with Indonesian language. Farah’s practice of intertextuality was pre-mediated, calculated and purposeful, allowing her to engage in digital authorship involving creativity, improvisation and consciousness as ingredients of agency. In the same vein, Farah’s practice of intertextuality allowed her to author the self as a contemplative religious individual. The research concluded with an appeal to policy makers and educational practitioners to respond to the learners’ changing learning landscape by re-defining the way we view learners/students, from merely a recipient of knowledge to an individual who has agency, identity and funds of knowledge that have to be acknowledged and appreciated in any process of curriculum design and its implementation on a daily basis.